An unusual assembled Pb(ii) meso-helicate that shows the inert pair effect. Issue 41 (30th September 2016) - Romero, María J.; Carballido, Rocío; Rodríguez-Silva, Laura; Maneiro, Marcelino; Zaragoza, Guillermo; González-Noya, Ana M.; Pedrido, Rosa
Abstract : We report on a meso-helicate exhibiting the inert pair effect for the first time, demonstrating that this effect must be considered for the controlled assembly of Pb(ii ) supramolecular helicates/mesocates. Abstract : A dinuclear Pb(ii ) mesocate has been prepared with an unprecedented four-coordinated kernel in which the Pb(ii ) lone pair is stereochemically active. This is the first time that this effect has been observed in a supramolecular Pb(ii ) helicate or meso-helicate.